ENVIRONMENTAL AWARENESS AND CONSUMER BEHAVIOUR– AN EMPIRICAL STUDY WITH REFERENCE TO CHENNAI CITY - Dr. K.S.Aram Valartha Nayaki, Dr.B.Revathy (International Journal of Advanced Science and Technology, 2020)
Environment is closely related with business. There is a constant ‘give and take’ relationship between environment and business. The business receives inputs, information and technology from the environment and gives it back in the form of outputs (goods and services). Consumer awareness on products marketed guide the purchase decision of green products. This study aims to examine the influence of consumers' environmental concerns, awareness of green product, price and brand image on their purchasing decisions of green products. Based on the data collected through a field survey, the paper makes an assessment of the extent of environmental awareness and consumer behaviour prevalent among consumers in Chennai and lists the findings of the study which provides fruitful insights of environment sustainability.